Culture and behavioral strategy - Das, T. K. (Emerald Publishing Limited : Information Age Publishing Inc., 2017)
This book series on Research in Behavioral Strategy will cover the essential progress made thus far in this admittedly fragmented literature and elaborate upon fruitful streams of scholarship. More importantly, the book series will focus on providing a robust and comprehensive forum for the growing scholarship in behavioral strategy. In particular, the volumes in the series will cover new views of interdisciplinary theoretical frameworks and models (dealing with all behavioral aspects), significant practical problems of strategy formulation, implementation, and evaluation, and emerging areas of inquiry. The series will also include comprehensive empirical studies of selected segments of business, economic, industrial, government, and nonprofit activities with potential for wider application of behavioral strategy. Through the ongoing release of focused topical titles, this book series will seek to disseminate theoretical insights and practical management information that will enable interested professionals to gain a rigorous and comprehensive understanding of the subject of behavioral strategy. Culture and Behavioral Strategy contains contributions by leading scholars in the field of behavioral strategy research. The 10 chapters in volume deal with a number of significant issues relating to the intersection of culture and behavioral strategy, covering topics such as cultural diversity and strategic choice, the cultural intelligence of executives, business model innovation in entrepreneurship, paradoxical frames in culture and behavioral strategy, culture in M&As, network citizenship behavior, and organizational routines. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on the confluence of culture and behavioral strategy.
Keywords: Management -- Cross-cultural studies.; Strategic planning -- Cross-cultural studies.; Organizational behavior -- Cross-cultural studies.; Culltural intelligence.; Business & Economics -- Strategic Planning.; Business strategy.; elektronické knihy; electronic books